(untitled) (Pedagogy of Higher and Secondary Education, 2009)
This article considers the theoretical-practical structure of the subject called “Art of The deep attention is paid to the consideration of discipline structure levels and the importance of their compliance, the practical aspect of using certain components, and their role in obtaining professional knowledge of students.